Hepatoprotective potential of Decalepis hamiltonii (Wight and Arn) against carbon tetrachloride-induced hepatic damage in rats - R Harish; T Shivanandappa (Wolters Kluwer Medknow Publications, 2010)
Hepatoprotective activity of the roots of Decalepis hamiltonii (Wight and Arn) was studied using carbon tetrachloride (CCl 4 ) induced liver injury model in albino rats. The hepatotoxicity produced by acute CCl 4 administration was found to be inhibited by pretreating the rats with crude methanolic extract of the roots of D. hamiltonii (Dh) prior to CCl 4 induction. Hepatotoxic inhibition was measured with the decreased levels of hepatic serum marker enzymes (glutamate-pyruvate transaminase (GPT), glutamate oxaloacetate transaminase (GOT), alkaline phosphatase (ALP), and lactate dehydrogenase (LDH) and lipid peroxide formation. Imbalance level of glutathione (GSH) and antioxidant enzymes such as catalase, glutathione peroxidase, and glutathione reductase were normalized in rats pretreated with Dh extract followed by CCl 4 administration. Pathological changes of hepatic lesions caused by CCl 4 were also improved by pretreatment with the Dh root extract. The results of this study indicate that roots of D. hamiltonii could afford a significant protective action in the alleviation of CCl 4 -induced hepatic damage in rats.